(untitled) (Indian Journal of Arid Horticulture, 2025)
Area of plantation of arid fruits is increasing every year under arid and semi-arid regions of the country. Fruit crops like ber; pomegranate, aonla, date palm and other minor fruits are mostly grown in water deficit areas. Among different production constraints in these crops, diseases are also concerned with yield and quality of fruits. For example, powdery mildew of ber can devastate whole orchards and fruit rots can trim down yield and quality of fruits. Leaf and fruit spots in pomegranate affect the foreign trade; rust in aonla results in poor quality of fruits in the absence of proper management practices in these crops. Low establishment of new plantation in date palm is mainly because of sucker rot in addition to fruit rot incited by common saprophytes. Despite, advancements in plant pathology and molecular plant pathology, much attempts have not been focused on etiology and management of arid zone fruits and therefore, presently a comprehensive information on biological control is discussed herewith.